Solve for the variable.Check solution.  -3(y-3y)+4=-4(3y-y)+6+13y

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`-3(y-3y)+4 =-4(3y-y)+6+13y`

Start by combining like terms inside the parentheses.

`-3(-2y) +4 = -4(2y) +6 +13y`

Multiply terms inside the parentheses by `-3` on the left side of the equation and `-4` on the right side of the equation.

`6y +4 = -8y +6 +13y`

Combine like terms on the...

See
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Sign Up for 48 Hours Free Access

`-3(y-3y)+4 =-4(3y-y)+6+13y`

Start by combining like terms inside the parentheses.

`-3(-2y) +4 = -4(2y) +6 +13y`

Multiply terms inside the parentheses by `-3` on the left side of the equation and `-4` on the right side of the equation.

`6y +4 = -8y +6 +13y`

Combine like terms on the right side of the equation.

`6y+4 = 5y +6`

Now subtract `5y` from both sides of the equation.

`1y +4 =6`

Subtract `4` from both sides of the equation.

`1y=2`

`y=2`

Check your solution by plugging your answer into the original equation.

`-3(2-3(2))+4 = -4(3(2)-2) +6 +13(2)`

`-3(-4) +4 = -4(4)+6+26`

`12+4=-16+6+26`

`16= -16+32`

`16=16`  Check

The solution is y=2.

 

 

Approved by eNotes Editorial Team